Breastfeeding in children with cleft lip and palate: Integrative review (Research, Society and Development, 2023)
Objective: to identify in the literature which factors are associated with adherence to exclusive breastfeeding in infants aged 0-6 months with cleft lip and/or palate. Method: integrative review. The search was carried out through the Virtual Health Library, in the databases of Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MedLine) and Database in Nursing (BDENf). The selection of articles was carried out through the Rayyan platform from December 2022 to January 2023. Results: It was identified through the articles, that after the parents received the necessary guidance and training regarding the use of some techniques such as food education in preschool natal, perinatal and postnatal, the use of palatine obturator, feeding plate, nipple protector, special bottle and spoon were evidenced as contributing factors for successful breastfeeding. Conclusion: few infants were exclusively breastfed and for the period recommended by the WHO. Identified that the receipt of guidance by health professionals in the prenatal, perinatal and postnatal period is extremely important and instigated in a favorable way, that is, the success of this practice is directly related to the complexity of the fissure, a non-modifiable factor, but, also, receiving guidance indicating that this is an intervention space to be explored. Also proving that with the appropriate techniques and equipment it is possible to successfully practice exclusive breastfeeding in children with cleft lip and/or palate.